Enfermagem: representação social das/os enfermeiras/os - Rodrigues, Maria Socorro Pereira (1998)
In this work, to start the thesis that the nurse and male nurses represents the nursing as being a profession whose importance is not recognized by the society. It takes for base, the revelation of the nurses and male nurse on its quotidian in the practical hospitais. It is guided by the theory of the Social Representations based in Moscovici. The sarnple is of the allcgory type, proportional stratifiedand characteristically probabilistic, composed by 29 nurses, and 01 male nurses, that work in two hospitais of great load, of the City of Fortaleza - Ceará. The collection of data took place starting from a semi-struetured interview, with tape recorder aid. that were analyzed with base in the referential of Bardin (1977) l he analysis originated two great themes: Nursing and social status and The professional nurse in its sociality, that strueture five sub-themes' I) nursing: hislory and professional evolution; 2) recognition and social valonzation of the nursing, 3) repercussion of the work nurses and male nurse in the society; 4) pcrsonal dimcnsions of the professional nurse and male nurses before the profession and the society, 5) image and feelings of the nurses and male nurses in the exercisc of the nursing. The social representations poínt for: a) existence of confront between historical context and evolution of the profession: b) dissonance between value and recognition of lhe nursing; c) existence of larger independence, aulonomy and understanding professional of the nurses and male nurses, d) necd of bctler understanding of the professional paper; e) the ignorance for the society of the paper of the nurses and male nurses; f) difficulty in the internai relationships among the members of the team; g) diversification of responsibilitics of the nurses and male nurses and long work days, precanous conditions of available material for the work, hand of work insufficient, low salaiy remuneration, they are factors that don t contribute to the efetivation of a larger satisfaction of the nurses and male nurses; h) the nursing provides pleasures and satisfaction of the nurses and male nurse, i) the activities of Teaching, she/he Researches, Public Health and Administrative Positions are more valued bv the society. The ambiguous context of the spccches, points for the need of larger social conscience, professional and political of the nurses and male nurses, in order to best to work with the polcmic subjects of the profession.